Método para identificação de oportunidades de melhoria em produtos através da avaliação de dados provenientes de cobertura de garantia - Bueno, Márcio Reginaldo (2013)
The needs imposed by the market demand that companies develop products more complex under the technological point of view, incorporating new functions to products already developed and continuously seeking to improve products and manufacturing processes to maintain its competitiveness. At the same step that is vital for a company to innovate and improve its products, it must be considered the wide use of engineering resources and costs associated with engineering changes, especially the poorly planned ones. The aim of this work is the creation of a method in order to support the decision-making for engineering changes by identifying opportunities for improvement on product that can be perceived by customers, using data from warranty records. As part of the methodological approach, a case study at a partner company in the automotive parts industry was used to identify opportunities for product improvement. The method uses data from warranty records (field data), which are analyzed in six different perspectives of failures concentration. Then, the application of the method in a hypothetical case was performed. This work contributes to the planning of engineering capacity, prioritizing of engineering changes with perceived value by the customer and the correct definition of the product according to the market application. With more reliable data, decision-making becomes more effective for managing certain engineering change, focusing on improving products that will actually be perceived by the customer. Thus, it can be set the right design requirements for a particular market, planning for resource allocation on different projects and prioritization of critical issues.